Inskripsi Islam pada Makam-Makam Kuno Barus - Pinem, Masmedia (Jurnal Lektur Keagamaan, 2018)
This article is an effort of re-reading of Islamic inscription in the tombs of Barus compared to the earlier works of the research. For this purpose, this research paper is limited to cultural traces over Arabic inscriptions drawn at the ancient tombs i.e. tomb of Mahligai, tomb of Tuan Makhdum, tomb of Ibrahimsyah, tomb of Papan Tinggi, and tomb of Sigambo-Gambo. In a course of reading such inscriptions of the tombs, he used several methods, such as descriptive technique, reading, and transliteration of the inscriptions and being ended by describing and analysing the final result of  the research. Descriptive studies done by description material culture, religious inscription, scripts, languages and meaning. Further, analysis used by comparing to other works with the data in the fields.Keyword: Barus, islamic inscription, ancient tomb, historical tracesTulisan ini berupaya menggambarkan dan menjelaskan inskripsi yang terdapat pada makam-makam kuno di Barus dengan cara membandingkan tulisan sebelumnya dengan titik bidiknya, seperti Makam Mahligai, Makam Tuan Makhdum, Makam Ibrahimsyah, Makam Papan Tinggi, dan Makam Sigambo-Gambo. Metode dan tahapan-tahapan yang dilakukan melalui beberapa cara yaitu, penyajian data secara deskriptif, pembacaan dan transliterasi inskripsi, dan terakhir pembahasan. Kajian deskriptif dilakuakan meliputi kondisi fisik, inskripsi keagamaan, aksara dan bahasanya, dan isinya. Sementara, pembahasan atau analisis dilakukan dengan membandingkan dengan bacaan-bacaan lain yang diperkaya data lapangan.Kata Kunci: Barus, inskripsi Islam, makam kuno, tinggalan sejarah